The Implementation Of Bellman-Ford Algorithm In Rembang Tourism Mobile Application As A Tourism Information Media (Data Science: Journal of Computing and Applied Informatics, 2019)
Tourism is one of the methods to publish the beauty of nature or the uniqueness of culture in a region that spreads from the coast up to the mountains. The distribution and the access to tourist attractions require mobile application. In creating the application, Bellman – Ford algorithm was used to get the shortest route. The algorithm was the Bellman – Ford algorithm which was used to calculate the shortest distance to the tourist attraction on the weighted graph. Testing the functionality of the application used a black box. The results showed that functions on the mobile application could run well. The compatibility testing showed 100% compatibility with a number of Android devices. In addition, the usability testing showed that the application was appropriate to use with percentage by 82.7% of the 30 respondents. The "Rembang tourism" mobile application can be used by users of information about tourism.